Comportamento do consumidor de comida japonesa: um estudo sobre atributos e valores - Sampaio, Joiza Angélica do Carmo (2009)
To know the reasons that motivate the consumer to choose determined product or service has been the main interest of organizations, marketing professionals and academics to intensify their researches in order to enlarge their prospects and possibilities related to the consumer behavior. This work got the goal to fully study the relation of value, understanding the connection among characteristics, consequences and values, realized by the food consumer of Fortaleza city. The Theoretical pillar is based that emphasizes the consumer behavior, values, hedonic consumption, and the Means and Ending Chain theory (MEC) that comes to highlight the proposed study for trying to focus the consumer behavior based on the relation between the characteristics of the product, the consequences and/or benefits throughout the use with their values of higher-level abstraction such as satisfaction, accomplishment, peace, safety. The technical tool is the so-called laddering, whose pillar is based on the implications in the MEC theory with the central concept of hand ladder, exploring the three levels, attribute (A); Consequences(C) Values – (V). Fifty interviews were deeply made with Japanese food consumer in Fortaleza City between the months of November 2008 and April 2009. The technical tool promoted the construction of an implication matrix as well as a value hierarchal map that allowed to highlight the elements that characterize such behavior. The research result had shown individual values among consumers as the opening for changing, exciting life, satisfaction, pleasure, self esteem, affective relation and friendship, confirming the search to get the personal satisfaction.